2013
DOI: 10.1128/iai.00886-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin II Receptor Blocker on Experimental Periodontitis in a Mouse Model of Marfan Syndrome

Abstract: Marfan syndrome is an autosomal dominant disease characterized by aneurysm and dilatation of the aortic root, tall stature, and ectopia lentis. These manifestations reflect excessive signaling of transforming growth factor beta (TGF-␤). Moreover, cases are frequently associated with severe periodontitis, which is a chronic inflammation of the gingiva, periodontal ligament, and alveolar bone. Recently, angiotensin II receptor blockers (ARBs) were discovered to be an effective drug class that can prevent aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
(56 reference statements)
0
30
0
Order By: Relevance
“…In a study by Suda et al. () that investigated the effect of TELM on the progression of periodontitis in a mouse model of Marfan syndrome, the authors concluded that treatment with TELM significantly suppressed alveolar bone resorption and decreased the levels of TGF‐β, IL‐17 and TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Suda et al. () that investigated the effect of TELM on the progression of periodontitis in a mouse model of Marfan syndrome, the authors concluded that treatment with TELM significantly suppressed alveolar bone resorption and decreased the levels of TGF‐β, IL‐17 and TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genome-wide association studies are helpful to identify novel genetic factors that contribute to intracranial aneurysm susceptibility. Consequently, it is possible to produce an aneurysm on cerebral vessels experimentally using genetic technology (Suda et al, 2013). Furthermore, ensuring reproducibility of results, the efficacy of a treatment option should be confirmed in multiple species and in multiple laboratories before beginning translation to a clinical study (Tajiri et al, 2013).…”
Section: Sah Backgroundmentioning
confidence: 99%
“…On the other hand, the recent knowledge on the inflammatory pathways involved in this disease has unleashed novel venues for therapy, with increased attention to strategies that modulate the inflammatory response 7. Recently, an anti-inflammatory effect was suggested for antihypertensive drugs (angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors, β-blockers) in periodontitis 8,9. More recently, the cholesterol-lowering drug simvastatin, used as adjuvant in hypertensive patients with dyslipidemia, was suggested to have a protective effect against experimental10,11 and human periodontitis 9,12.…”
Section: Introductionmentioning
confidence: 99%